Relação com o saber de estudantes da educação de jovens e adultos: mobilização, sentido e relações com o aprender - Jesus, Charlene Pereira de (2023)
This research is anchored in Bernard Charlot's theory of the relationship with knowledge and subsidized by scholars of education, such as Paulo Freire and Lev Vygostky. It seeks to understand the relationship with knowledge and student history of students of Youth and Adult Education. The studies carried out tried to answer the central question of this research: what is the relationship of youth and adult education students with knowledge and what motivated them to return to formal learning spaces? In this sense, from the theoreticalmethodological point of view, such studies are consistent with an exploratory research of a qualitative nature and used as data collection instruments: observation, knowledge balance and interviews. The research subjects are students of the sixth year of the EJA of a Municipal School of Paripiranga - BA. The research presented here proposed the study and reflection on the relationships of EJA students with knowledge, seeking: 1 to enter into the student history of these students who are returning to school; 2. tried to understand what mobilizes them in this return; 3. How the school has dealt with the diversity of knowledge brought by them from their daily lives. It is hoped that the results of this research will contribute to scientific research, providing other researchers with access to yet another source of information about EJA.